Exploring the Use of Antenatal and Maternity Services by Mothers Engaged in Child Welfare Programs in Michika LGA, Adamawa State - Isaac John Umaru; Solomon O. Asare; Tyem Lawal Danjuma; Julius Ishaya Salman; Ingwu Joseph Akem; Genevieve A. Yeboah; Prince Osei Akumia; Hauwa A. Umaru; Maryam Usman Ahmed (Darul Yasin Al Sys, 2026)
Maternal health remains a critical public health concern in Nigeria, where high rates of maternal morbidity and mortality persist despite ongoing interventions. This study aimed to assess the level of awareness and utilization of maternal health services among women in Wukari, Taraba State, Nigeria, to identify key barriers to service uptake, and to evaluate the influence of child welfare programs on antenatal care utilization. A cross-sectional descriptive survey was conducted among 250 women of reproductive age using structured questionnaires. Data were collected on socio-demographic characteristics, antenatal and maternity service utilization, barriers to access, and participation in child welfare programs, and were analyzed using descriptive statistics to generate frequencies and percentages. The findings showed that 85% of respondents were aware of antenatal services and 80% attended antenatal care during their last pregnancy; however, only 30% completed more than four visits. Skilled birth attendance was reported by 68% of respondents, whereas 16% delivered at home or with traditional birth attendants, and 60% received post-natal care. The major barriers to service utilization included distance to health facilities (60%), financial constraints (44%), lack of transportation (36%), poor attitude of health workers (28%), cultural and religious beliefs (24%), and lack of awareness (16%). In addition, women who participated in child welfare programs were 30% more likely to utilize antenatal services. These findings indicate that, despite relatively high awareness, maternal health service utilization remains suboptimal because of intersecting structural, economic, and sociocultural barriers. The study underscores the need to strengthen health infrastructure, improve transportation access, subsidize care, and expand community-based interventions, while also addressing cultural beliefs and health worker attitudes to improve maternal health outcomes in rural Nigeria.